Every leaf, line, and letter : Evangelicals and the Bible from the 1730s to the present - Larsen, Timothy, 1967- (IVP Academic, 2021)
"Christians within evangelicalism have always had a high regard for the Bible. How has the eternal Word of God been received across various races, age groups, genders, nations, and eras? This collection of historical studies focuses on evangelicals' defining uses-and abuses-of Scripture, from Great Britain to the Global South, from the high pulpit to private devotions and public causes"--